C(sp3)–C(sp3) coupling polymerization of alkyl dibromides for preparation of polymers with precisely located phenyl pendants. (1st May 2015) - Zou, Lei; Long, Meilin; Zhou, Houbo; Zhu, Wen; Zhang, Ke; Chen, Yongming; Xi, Fu
Abstract: Recently it was reported that C(sp 3 )Br–C(sp 3 )Br homo-coupling reactions may be occurred efficiently catalyzed by Ni(II) in the presence of Zn. In this work, we applied this reaction for polymerization of alkyl dibromides. It was shown that 1, 4-dibromobutane may polymerize by this coupling polymerization to afford polybutenes with low molecular weight. Then dl -1, 4-dibromo-2, 3-diphenylbutane, 1, 3-dibromo-2-phenylpropane and dl -1, 4-dibromo-2-phenylbutane were polymerized by the C(sp 3 )–C(sp 3 ) coupling reaction under optimized condition. As a result, head-to-head polystyrene, poly(methylene- alt -styrene), and poly(ethylene- alt -styrene) were obtained. The number average molecular weights relatively to polystyrene standards may reach ca. 6000 Da. These polymers with strictly controlled sequential structures were characterized by proton and carbon nuclear magnetic resonance spectroscopy and matrix-assisted laser-desorption-ionization time-of-flight mass. Glass transition temperature was obtained by running differential scanning calorimetry. Graphical abstract: Highlights: C(sp 3 )Br–C(sp 3 )Br coupling reaction was applied for polymerization of alkyl dibromides. C(sp 3 )–C(sp 3 ) coupling polymerization of 1, 4-dibromobutane gives polyethylene. It is applied to prepare a series of polyhydrocarbons with precisely controlled location of phenyl pendants.